UTILIZING CRITICAL DISCOURSE ANALYSIS ON DEVELOPING STUDENTS' DIGITAL LITERACY SKILLS: AN ACTION RESEARCH - Oktarin, Irene Brainnita; Hastomo, Tommy (Premise: Journal of English Education and Applied Linguistics, 2024)
In today's digital era, students need digital literacy skills to critically navigate, evaluate, and analyze a large amount of online information. Digital literacy uses digital technology to obtain, evaluate, create, and communicate information in various contexts. This research aimed to investigate the impact of CDA in improving students' digital literacy, explore the role of CDA in enhancing students' digital literacy, and identify the lecturer's strategy in using CDA for enhancing students' digital literacy. This current study used classroom action research as a research design which consisted of two cycles. The participants in this research were college students at STIE Gentiaras Lampung. The instruments of this research consisted of tests and non-test. Quantitative data was taken from students' digital literacy tests, and qualitative data were taken from observation and interviews. The findings show that CDA can improve students' digital literacy. Moreover, there were five roles of CDA in enhancing students' digital literacy: fostering critical thinking, promoting media literacy, enhancing textual analysis, encouraging social awareness, and cultivating responsible digital citizenship. The last finding is the teacher employed three strategies to improve students' digital literacy: acquainting them with the fundamental principles of CDA, selecting diverse texts for comprehensive CDA analysis, and encouraging classroom discussions. According to the findings, policymakers can consider integrating CDA into educational curricula to enhance students' digital literacy skills.